2020
DOI: 10.1108/ijopm-07-2019-0530
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity and its coping mechanisms in supply chains lessons from the Covid-19 pandemic and natural disasters

Abstract: PurposeThe first purpose of this paper is to situate and conceptualise ambiguity in the operations management (OM) literature, as connected to supply chain decision-making (SCDM). The second purpose is to study the role of ambiguity-coping mechanisms in that context.Design/methodology/approachThis research uses the behavioural decision theory (BDT) to better embed ambiguity in a generic SCDM framework. The framework explicates both behavioural and non-behavioural antecedents of ambiguity and enables us to also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 56 publications
(150 reference statements)
5
123
0
Order By: Relevance
“…In order to create value for customers, Mollenkopf et al (2020) used a service-dominant logic paradigm to prepare a supply chain response plan to the current food crisis. The behavioral decision theory is used to understand how organizations behave and make decisions during ambiguous events such as the COVID-19 pandemic ( Gunessee and Subramanian, 2020 ).…”
Section: Analyzing the Reviewed Articles On The Covid-19 Pandemic In mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to create value for customers, Mollenkopf et al (2020) used a service-dominant logic paradigm to prepare a supply chain response plan to the current food crisis. The behavioral decision theory is used to understand how organizations behave and make decisions during ambiguous events such as the COVID-19 pandemic ( Gunessee and Subramanian, 2020 ).…”
Section: Analyzing the Reviewed Articles On The Covid-19 Pandemic In mentioning
confidence: 99%
“…A report published by Fortune magazine on 21 February 2020, before the WHO reclassified the COVID-19 outbreak as a pandemic on 11 March 2020, revealed that due to the COVID-19 pandemic, 94% of the Fortune 1000 companies were facing disruption in their supply chains ( Fortune, 2020 ). Moreover, unlike other previous outbreaks, this pandemic has impacted all the nodes (supply chain members) and edges (ties) in a supply chain simultaneously ( Gunessee and Subramanian, 2020 , Paul and Chowdhury, 2020a ); hence, the flow of the supply chain has been disrupted substantially. For example, the demand for necessary items such as personal protective equipment (PPE), ventilators, and dried and canned foods has increased.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, suppliers should have the capability to adapt to changes in market demand (such as customer preferences) and the capability to remain competitive through new product development (Zsidisin and Ellram, 2003;He et al, 2020). Moreover, a recent study suggested that the negative effects of the COVID-19 pandemic lockdown on global supply disruption came from having a complex supply network that was subject to many human errors and safety concerns (Gunessee and Subramanian, 2020). In presented here provides the most comprehensive assessment of supply chain disruption risks in terms of capturing different types of risks in a supply chain.…”
Section: Supply Disruptionmentioning
confidence: 99%
“…Demand variations such as changes in order quantity, shorter product life cycle, and the introduction of new products pose significant risks to the firm (Ho et al, 2005;Manuj and Mentzer, 2008). COVID-19 showed that customers who engage in panic buying and social distancing cause volatility in demand with a ripple effect in supply chains (Gunessee and Subramanian, 2020) A fundamental activity in a supply chain is to properly match demand and supply. Demand disruption also occurs when a firm is not able to properly match supply and demand, as a result of either forecast inaccuracy, a ripple effect, or from inefficient coordination in the supply chain (Chen et al, 2013).…”
Section: Demand Disruptionmentioning
confidence: 99%
See 1 more Smart Citation